2012
DOI: 10.1080/13825585.2011.638975
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in word-retrieval but not in meaning generation

Abstract: This study examines age-associated changes in retrieval on a picture-naming task, phonemic and semantic fluency tasks, and the Homophone Meaning Generation Test (HMGT). The sample included 152 Hebrew-speaking adults, half young (mean age 22.75) and half old (mean age 76.05). Groups differed on the picture-naming task and on both verbal fluency tasks, but not on the HMGT. Age explained a greater share of the variance than did education level on these three tests, whereas the opposite pattern of results was seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Future research should examine whether similar findings emerge when speech is elicited with no pictorial support, for example, by asking participants to recall a personal experience. Second, the verbal fluency task is highly dependent on executive functions (Kavé, Heled, Vakil, & Agranov, 2011), perhaps more so than it depends on semantic stores (Kavé & Mashal, 2012). Hence, the lack of correlations between semantic fluency scores and measures of connected speech could reflect the fact that retrieval difficulties in connected speech in AD are determined more by semantic difficulties and less by impairment in executive control.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should examine whether similar findings emerge when speech is elicited with no pictorial support, for example, by asking participants to recall a personal experience. Second, the verbal fluency task is highly dependent on executive functions (Kavé, Heled, Vakil, & Agranov, 2011), perhaps more so than it depends on semantic stores (Kavé & Mashal, 2012). Hence, the lack of correlations between semantic fluency scores and measures of connected speech could reflect the fact that retrieval difficulties in connected speech in AD are determined more by semantic difficulties and less by impairment in executive control.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that semantic processing remains stable in old age in language comprehension and production (Kavé and Mashal, 2012;Ramscar et al, 2014;Lacombe et al, 2015) since semantic process of language benefits from verbal knowledge (i.e., vocabulary and semantic memory) adults have acquired over years (Verhaeghen, 2003;Ben-David et al, 2015). Compared to young adults, older adults presented comparable performance in semantic processing tasks including semantic judgment (Little et al, 2004), semantic priming task (Gold et al, 2009), lexical decision task (Gold et al, 2009), and picture naming (Kavé and Mashal, 2012). Farrell (2012) compared semantic priming of TOTs occurrence for word production in young and older adults, and did not find the effect of semantic priming on TOTs for either age group, reflecting that TOTs are little associated with word's semantics (see also Cross and Burke, 2004).…”
Section: Asymmetries Of Semantic and Phonological Retrieval In Old Agementioning
confidence: 99%
“…Previous studies have reported an association of semantic fluency with processing speed [17,24,25], lexical access [25–27], executive functions [26,28], and working memory [25]. Phonemic fluency has been reported to be associated with processing speed [17,24,25], attention [13,29], lexical access [27], executive functions [26,2831], and memory [29,32]. Studies on action fluency did not find an association with episodic memory or picture naming [12,23].…”
Section: Introductionmentioning
confidence: 99%